System Literatur Review : Peran Filsafat Ilmu Terhadap Pembelajaran Pendidikan Jasmani - Ilmi Legismawati Pauzi; Agis Darmawan; Dhea Mahsa; Muhammad Fathurahman; Carsiwan, Carsiwan (CV. ITTC INDONESIA, 2025)
Abstract Physical Education is a field of education that plays an important role in holistic human development, encompassing physical, cognitive, affective, and social aspects. However, in practice, physical education is often understood narrowly as merely physical activity, thus ignoring the philosophical foundations that underlie the development of science and its learning practices. This article aims to systematically analyze the role of philosophy of science in physical education learning in schools through a Systematic Literature Review (SLR) approach. The SLR method is carried out by identifying, selecting, and synthesizing relevant scientific articles from reputable national databases in the 2020–2025 period. A total of 8 selected articles were analyzed using a prism model. The results show that philosophy of science has an important role in physical education learning in schools: (1) clarifying the nature of physical education as a holistic educational process, (2) strengthening the epistemological foundation in curriculum development and scientific-based learning, and (3) emphasizing the axiological dimension through the internalization of ethical, moral, and character values. This article is expected to be a theoretical reference for the development of physical education policies, curricula, and practices. Keywords: Philosophy of Science, Learning, Physical Education Abstrak Pendidikan Jasmani merupakan bidang pendidikan yang berperan penting dalam pengembangan manusia secara holistik, mencakup aspek fisik, kognitif, afektif, dan sosial. Namun, dalam praktiknya, pendidikan jasmani masih sering dipahami secara sempit sebagai aktivitas fisik semata, sehingga mengabaikan landasan filosofis yang menjadi dasar pengembangan ilmu dan praktik pembelajarannya. Artikel ini bertujuan untuk menganalisis secara sistematis peran filsafat ilmu terhadap pembelajaran pendidikan jasmani di sekolah melalui pendekatan Systematic Literature Review (SLR). Metode SLR dilakukan dengan mengidentifikasi, menyeleksi, dan mensintesis artikel ilmiah yang relevan dari basis data nasional bereputasi pada rentang tahun 2020–2025. Sebanyak 8 artikel terpilih dianalisis menggunakan model prisma. Hasil menunjukan bahwa filsafat ilmu memiliki peran penting dalam pembelajaran pendidikan jasmani di sekolah (1) memperjelas hakikat pendidikan jasmani sebagai proses pendidikan holistik, (2) memperkuat landasan epistemologis dalam pengembangan kurikulum dan pembelajaran berbasis ilmiah, serta (3) menegaskan dimensi aksiologis melalui internalisasi nilai etika, moral, dan karakter. Artikel ini diharapkan menjadi rujukan teoretis bagi pengembangan kebijakan, kurikulum, dan praktik pendidikan jasmani. Kata kunci: Filsafat Ilmu, Pembelajaran, Pendidikan jasmani